2019
DOI: 10.18203/2320-6012.ijrms20194193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of perioperative morbidities of the conventional and ultrasound-guided suprapubic catheterization in the patients of urinary retention during emergency

Abstract: Background: Urinary retention is one of the common urological emergencies and conventional ‘blind’ SPC frequently used comfortable as well superior procedure for patients. During conventional SPC, the distended bladder is identified by palpation or percussion without proper attention to intervening bowel segment and other structures. However, the recently published data suggests that if, ultrasound is used during SPC, and it identifies not only bladder but also intervening bowel segment which complications. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
(15 reference statements)
2
2
0
Order By: Relevance
“…In another study, it was reported that the USG-assisted technique was simple, safe, effective and associated with minimal complications [8]. In two studies comparing direct blind and USG-assisted techniques in the literature, the ultrasonography procedure was found to be safer, which is consistent with our study [5,6]. In our study, no difference was found between the two techniques in the groups except for early complications.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In another study, it was reported that the USG-assisted technique was simple, safe, effective and associated with minimal complications [8]. In two studies comparing direct blind and USG-assisted techniques in the literature, the ultrasonography procedure was found to be safer, which is consistent with our study [5,6]. In our study, no difference was found between the two techniques in the groups except for early complications.…”
Section: Discussionsupporting
confidence: 90%
“…Causes of urinary retention include benign prostatic hyperplasia (BPH), urethral stricture, prostate cancer, clot retention, stone and neurological bladder [7]. In two studies reported in the literature, urethral stricture and BPH were determined as the most common causes of urinary retention in patients with PSCC, respectively, and there was only one female patient in both study populations [5,8]. Similarly, the most common etiological factor in our series was urethral stricture, and the second was BPH.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations